UTILISATION OF MOLECULAR MARKERS FOR DETERMINING MANAGEMENT STRATEGIES OF THE BLOOD COCKLE, Anadara Granosa - Ghani, Farhana Mohd (2011)
A population genetic study of the blood cockle, Anadara granosa, on the west coast of Peninsular Malaysia was conducted to define the genetic structuring and determine temporal variation between year classes (2007/2008 and 2008/2009) of this species. In addition, novel microsatellite markers were developed. The population investigation was based on the Cytochrome Oxidase subunit I mitochondrial DNA (COI mtDNA) marker that had previously used to infer population structuring of adult A. granosa.